THE NATURE OF LAW AND JUSTICE IN SOCIETY - Kholiq, Abdul; Purnomo, Heri (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2023)
At this time globalization has penetrated the dynamics of human life and brought changes that essentially point to the problem of unbalanced regulation of human life in law and a sense of human justice. In everyday life we often hear people demanding justice, because they feel they have received unfair treatment. This can occur between citizens and the government, or perhaps also between individuals and their groups or because there are differences in the fulfillment of personal rights and so on. Justice is closely related to attitudes and relationships with fellow human beings because justice demands that every human being be treated as they are done. The problem is How is the nature of law and justice related to the philosophy of law and How is the form of justice pursued by judges? The method used in writing this paper is normative juridical, which is an approach based on law as the main material, the research specification used is descriptive analytical, which is research that aims to provide an overview of justice in Indonesia. While the data sources are secondary and primary data through primary field studies used as supporting data or supporting secondary data. From the research, the results were obtained: The nature of law and justice is very relative, because from which side we look at it there is a negative that law and justice are something that is not heavy after there are also those who say that justice is not necessarily found with field results and the form of justice in this case can be done by judges and rulers by trying to comply with laws and regulations and a sense of public justice, but judges are ordinary human beings who can make mistakes. Mistakes can occur due to inadvertence and can also be made can arise from people who are deliberate, this is what will plunge humans. True justice is the justice of Allah SWT.